1985
DOI: 10.1002/jcp.1041250329
|View full text |Cite
|
Sign up to set email alerts
|

Commitment to differentiation of human promyelocytic leukemia cells (HL60): An all‐or‐none event preceded by reversible losses of self‐renewal potential

Abstract: A method for clonal analysis has been developed which allows the characterization of the number and type of progeny cells produced by each single cell arising during clonal evolution. The method is based on a symmetry of self-renewal exhibited by sister cells of the human promyelocytic leukemia cell line -HL60-. This permits the use of one of the sister cells to measure the potential for self renewal of the other. Using a system of sequential daughter cell transfers in semisolid medium, we have analysed self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The granulocytic maturation these cells undergo in response to chemical agents, such as DMSO, has been well characterized (3). In addition to the induction of a series of lineage-specific phenotypic properties, maturation is associated with the loss of self-renewal capacity in these cells (8,37,38). The loss of self-renewal capacity has been reported to be a distinct cellular event that occurs before the commitment of the cells to differentiation (8,38).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The granulocytic maturation these cells undergo in response to chemical agents, such as DMSO, has been well characterized (3). In addition to the induction of a series of lineage-specific phenotypic properties, maturation is associated with the loss of self-renewal capacity in these cells (8,37,38). The loss of self-renewal capacity has been reported to be a distinct cellular event that occurs before the commitment of the cells to differentiation (8,38).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the induction of a series of lineage-specific phenotypic properties, maturation is associated with the loss of self-renewal capacity in these cells (8,37,38). The loss of self-renewal capacity has been reported to be a distinct cellular event that occurs before the commitment of the cells to differentiation (8,38). In this study, we have observed the stimulation of a family of genes which are associated with IFN treatment, including 2-5A synthetase activity, 2-SA phosphodiesterase activity, and HLA-B antigen expression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The number of S + G2 + M-phase cells remained low, be- (6), suggested that reversible losses of selfrenewal capacity precede irreversible phenotypic differentiation. The limitation of the experimental approach in both cases is that it does not allow for detection of regrowth of relatively few cells in liquid culture after prolonged reculture without inducer.…”
Section: Reculture Of Hl-60 Cells After a 96-hour Ra Incubationmentioning
confidence: 99%
“…The human myeloid leukemic cell line HL-60 (1) is a bipotential cell that can be differentiated by various agents either to the monocytic or granulocytic pathway (2 of differentiation, which are not necessarily coupled (3)(4)(5), and by using clonal assays after exposing cells to dimethylsulfoxide and retinoic acid (6,7). The present study takes a different experimental approach by using whole cell populations in liquid culture as the differentiation target.…”
Section: Introductionmentioning
confidence: 99%